Relationship between scrotal circumference and semen parameters in crossbred bulls (Bangladesh Veterinarian, 2010)
The relationship between the scrotal circumference and semen volume, sperm concentration and number of sperm per ejaculate of 12 crossbred bulls [4 Local × Friesian, 4 Local × Sahiwal] was studied. Semen of three consecutive collections at seven day intervals was evaluated. The age of bulls at first collection varied between 15 and 20 months. Soon after collection, volume, sperm concentration, number of spermatozoa per ejaculate and initial sperm motility of fresh semen were measured. Scrotal circumference was correlated with semen volume, sperm concentration and number of spermatozoa per ejaculate in both groups. A significant (P